Sistem Enkapsulasi Maltodekstrin-Kitosan pada Ekstrak Kulit Kakao (Theobroma cacao Linn.) yang Ramah Lingkungan untuk Inhibisi Korosi pada Baja dalam Media Korosif - Gusti, Diah Riski; Toyyibah, Fida; Nizori, Addion; Restianingsih, Tika; Faiquzzaky, Faiz; Tajuddin, Nazrizawati Ahmad (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2025)
This research tested an encapsulated cocoa husk extract formulated with maltodextrin and chitosan at an 8:2 ratio for use as a steel corrosion inhibitor. The method of weight loss in 0.75 M sulfuric acid, seawater, and peat water solutions was used to test inhibitors. The analysis indicated that inhibitor efficiency increased with increasing concentration. At the same time, its efficiency decreased due to longer immersion periods, reaching a maximum of 94.07% in peat water when a 2.5 g/L concentration of inhibitors was applied for 1 day. These results indicate significant potential for encapsulated cocoa husk extract as a natural corrosion inhibitor